2019
DOI: 10.1177/0146167219853842
|View full text |Cite
|
Sign up to set email alerts
|

On the Roles of Stereotype Activation and Application in Diminishing Implicit Bias

Abstract: Stereotypes can influence social perception in undesirable ways. However, activated stereotypes are not always applied in judgments. The present research investigated how stereotype activation and application processes impact social judgments as a function of available resources for control over stereotypes. Specifically, we varied the time available to intervene in the stereotyping process and used multinomial modeling to independently estimate stereotype activation and application. As expected, social judgme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Second, it would be interesting to study how different manipulations affect the model parameters as a function of the time available for stimulus processing and/or responding. For instance, previous research has shown that stereotype activation increases with longer time intervals in the SMT, because prime pictures are processed more thoroughly (Rivers et al, 2019). Conversely, stereotype application decreases with longer time intervals in the SMT, possibly because people are better able to control unwanted influences of activated stereotypes on judgments when more time is available.…”
Section: Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, it would be interesting to study how different manipulations affect the model parameters as a function of the time available for stimulus processing and/or responding. For instance, previous research has shown that stereotype activation increases with longer time intervals in the SMT, because prime pictures are processed more thoroughly (Rivers et al, 2019). Conversely, stereotype application decreases with longer time intervals in the SMT, possibly because people are better able to control unwanted influences of activated stereotypes on judgments when more time is available.…”
Section: Future Directionsmentioning
confidence: 99%
“…Because we did not find clear-cut results with respect to SAP in the previous experiment with ISI = 50 ms, we decreased ISI to 0 ms. We reasoned that with a shorter ISI the likelihood of controlled processing may be reduced (cf. Rivers et al, 2019), thereby providing better conditions to isolate the effects of prototypicality on stereotype activation. Because of the additional ISI-manipulation, the number of trials was increased to 216.…”
Section: Effects Of Prime Prototypicality: a Conceptual Replication Smentioning
confidence: 99%
See 1 more Smart Citation
“…Second, it would be interesting to study how different manipulations affect the model parameters as a function of the time available for stimulus processing and/or responding. For instance, previous research has shown that stereotype activation increases with longer time intervals in the SMT, because prime pictures are processed more thoroughly (Rivers et al, 2019). Conversely, stereotype application decreases with longer time intervals in the SMT, possibly because people are better able to control unwanted influences of activated Stereotype Misperception Task 34 stereotypes on judgments when more time is available.…”
Section: Future Directionsmentioning
confidence: 99%
“…Building on this initial research, the SMT together with the multinomial model has been used in a growing number of studies on stereotyping (Rees, Ma, & Sherman, 2019;Rivers, Sherman, Rees, Reichardt, & Klauer, 2019).…”
mentioning
confidence: 99%